Transcription factor CsDOF regulates glutamine metabolism in tea plants (Camellia sinensis). (January 2021) - Wang, Jinhe; Chen, Wenzhen; Wang, Hanyue; Li, Yuanda; Wang, Biao; Zhang, Lixia; Wan, Xiaochun; Li, Min
Highlights: A DOF-encoding gene CsDOF and a glutamine synthetase gene CsGS2 was identified in tea plant, respectively. CsDOF is a zinc finger protein and a light-responsive transcription factor. CsGS2 is a key gene of glutamine accumulation in tea leaves. CsDOF could indirectly regulate the expression of CsGS2 to impact on the glutamine accumulation in tea plants Abstract: Glutamine plays a critical role in ammonium assimilation, and contributes substantially to the taste and nutritional quality of tea. To date, little research has been done on glutamine synthesis in tea plants. Here, a zinc finger protein CsDOF and a glutamine synthetase (GS)-encoding gene CsGS2 from tea plant ( Camellia sinensis cv 'Shuchazao') were characterized, and their role in glutamine biosynthesis was determined using transient suppression assays in tea leaves and overexpression in Arabidopsis thaliana . The expression patterns of CsDOF and CsGS2, the GS activity and the glutamine content of photosynthetic tissues (leaf and bud) were significantly induced by shade. Suppressing the expression of CsDOF resulted in downregulated expression of CsGS2 and reduction of the leaf glutamine content. Moreover, in CsDOF- silenced plants, the expression of CsDOF and the glutamine content under shade treatment were higher than in natural light. The glutamine content and CsGS2 transcript level were also decreased in tea leaves when CsGS2 was suppressed, while they were higher under shade treatment than in natural light in CsGS2- silenced plants. In addition, the glutamine content and GS2 transcript level were increased when CsDOF and CsGS2 was overexpressed in Arabidopsis thaliana, respectively. In binding analyses, CsDOF directly bound to an AAAG motif in the promoter of CsGS2, and promotes its activity. The study shed new light on the molecular mechanism by which CsDOF activates CsGS2 gene expression and contributes to glutamine biosynthesis in tea plants.